1999
DOI: 10.1016/s0306-4522(99)00304-8
|View full text |Cite
|
Sign up to set email alerts
|

Early polysynaptic potentiation recorded in the dentate gyrus during an associative learning task

Abstract: potentiation recorded in the dentate gyrus during an associative learning task. Neuroscience, Elsevier

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
12
1
1
Order By: Relevance
“…Our data do not confirm those of Chaillan et al (1999) who reported potentiation of a polysynaptic response in the DG during learning. However, it is important to note that in our study, a recording session began 1 h after a training session; whereas Chaillan et al (1999) recordings were done immediately after the training session.…”
Section: Mouly and Gervaiscontrasting
confidence: 57%
See 2 more Smart Citations
“…Our data do not confirm those of Chaillan et al (1999) who reported potentiation of a polysynaptic response in the DG during learning. However, it is important to note that in our study, a recording session began 1 h after a training session; whereas Chaillan et al (1999) recordings were done immediately after the training session.…”
Section: Mouly and Gervaiscontrasting
confidence: 57%
“…However, it is important to note that in our study, a recording session began 1 h after a training session; whereas Chaillan et al (1999) recordings were done immediately after the training session. In the latter study, the observed potentiation was maximal just after each training session and decreased to a lower level when measured 24 h later.…”
Section: Mouly and Gervaismentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, polysynaptic responses were unchanged prior to and immediately following session 3. Furthermore, this polysynaptic potentiation was correlated to learning (Chaillan et al 1999). The decrease in Kv1.1 mRNA observed in the current study following session 2 and not session 3 may contribute to the dynamic activation of the hippocampal circuitry during associative information processing.…”
Section: Discussionmentioning
confidence: 99%
“…In the examination of olfactory pathways, an analysis was performed on regions believed to be necessary for the learning and memory of olfactory associative tasks (olfactory bulb, Ammon's horn, and dentate gyrus) (Chaillan et al 1999;Truchet et al 2002), as well as in the three animal groups (naive group, pseudoconditioned group, and conditioned group). The Kv1.1 mRNA level was analyzed in the olfactory bulb and in three structures of the dorsal and ventral hippocampus (dentate gyrus, CA3 and CA1) of rats sacrificed at three stages of learning, i.e., 1 h after session 2, 4 h after the session 2, and 1 h after session 3.…”
Section: Comparison Of Kv11 Mrna Levels Between the Groupsmentioning
confidence: 99%